Circulating osteogenic progenitors and osteoclast precursors are associated with long-term glycemic control, sex steroids, and visceral adipose tissue in men with type 2 diabetes mellitus - Ballato, Elliot; Deepika, Fnu; Prado, Mia; Russo, Vittoria; Fuenmayor, Virginia; Bathina, Siresha; Villareal, Dennis T.; Qualls, Clifford; Armamento-Villareal, Reina (Frontiers in Endocrinology, 2022)
Introduction: Type 2 diabetes mellitus (T2DM) is well-known to be associated with normal bone density but, concurrently, low bone turnover and increased risk for fracture. One of the proposed mechanisms is possible derangement in bone precursor cells, which could be represented by deficiencies in circulating osteogenic progenitor (COP) cells and osteoclast precursors (OCP). The objective of our study is to understand whether extent of glycemic control has an impact on these cells, and to identify other factors that may as well. Methods: This was a secondary analysis of baseline data from 51 male participants, aged 37-65 in an ongoing clinical trial at Michael E. DeBakey VA Medical Center, Houston, Texas, USA. At study entry serum osteocalcin (OCN) and C-terminal telopeptide of type 1 collagen (CTx) were measured by ELISA, and testosterone and estradiol by liquid-chromatography/mass-spectrometry. Areal bone mineral density (BMD), trabecular bone score and body composition were measured by dual energy x-ray absorptiometry, while COP and OCP were measured by flow cytometry. Results: When adjusted for serum testosterone, parathyroid hormone, and 25-hydroxyvitamin D, those with poor long-term glycemic control had significantly higher percentage of COP (p = 0.04). COP correlated positively with visceral adipose tissue (VAT) volume (r = 0.37, p = 0.01) and negatively with free testosterone (r = -0.28, p = 0.05) and OCN (r = -0.28, p = 0.07), although only borderline for the latter. OCP correlated positively with age, FSH, lumbar spine BMD, and COP levels, and negatively with glucose, triglycerides, and free estradiol. Multivariable regression analyses revealed that, in addition to being predictors for each other, another independent predictor for COP was VAT volume while age, glucose, and vitamin D for OCP. Conclusion: Our results suggest that high COP could be a marker of poor metabolic control. However, given the complex nature and the multitude of factors influencing osteoblastogenesis/adipogenesis, it is possible that the increase in COP is a physiologic response of the bone marrow to increased osteoblast apoptosis from poor glycemic control. Alternatively, it is also likely that a metabolically unhealthy profile may retard the development of osteogenic precursors to fully mature osteoblastic cells.